Mở rộng lớp các số Mersenne - Tân, Lều Đức (Journal of Computer Science and Cybernetics, 2016)
In this paper we investigate a class of nature numbers denoted by LM which properly includes the class of Mersenn ones. For this class, we propose an algorithm for testing primality. The algorithm works in polynomial time according to input belonging to LM. The problem that whether or not LM contains infinitely-many primes, even under the generalized Riemann hypothesis is open one.